Spatial Analysis Study on the Flood Impact of Walanae Cenranae River Area in Soppeng Regency South Sulawesi Province - Faisal, Zulvyah; Azis, Akhmad; Subhan, Andi Muhammad; Badaruddin, Sugiarto; Puspita, Devi Ayu (Politeknik Negeri Ujung Pandang, 2020)
Cabenge River is part of the WalanaeCenranae River area in Soppeng Regency. Annually, the area around the Cabenge River gets the most losses from floods, both in terms of facilities and infrastructures. This study aims to map the areas prone to flood and flood risk, based on the field that gets the most significant impact. This study uses a Geographic Information System (GIS) as a tool and ArcGis Software in determining the level of vulnerability and risk of flooding at the study site. This type of research is a combination of mapping (topographic results) and map analysis. The variables used are DEM (Digital Elevation Model) data and flood volume. The data processing technique used is the GIS-based inundation model approach using inundation height (H) based on a comparison between the volume of water (V) in inundated areas and the volume of water (Q) of flood sources. The results showed that Lilirilau District was in the high hazard class with an area of 100 km2 and had the biggest impact, while in Liliriaja District, the area that was in a high hazard class was 34 km2 and Ganra District was 21 km2.